Autoimmune Pancreatitis Presenting with Mass and Biliary Obstruction - Frank, Amber A. (Radiol Case Rep, 2015)
We report a case of autoimmune pancreatitis in a 31-year-old man with signs and symptoms of biliary tract obstruction. Evaluation with sonography, computed tomography, and ultimately endoscopic retrograde cholangiopancreatography, demonstrated a 5 by 2 cm hypoechoic, hypodense mass near the head of the pancreas that extended into the porta hepatis. Common bile duct obstruction with proximal dilatation was present. Following fine needle aspiration of the mass, cytology showed findings consistent with autoimmune pancreatitis. Treatment with common bile duct stent was followed by resolution of the patient's symptoms.